LISTENING FROM PLACES OF SURVIVAL: THE ROLE OF STORY LISTENING IN THE EMPOWERMENT OF FEMALE VICTIMS OF VIOLENCE. Issue 3 (2nd September 2019) - Brazelton, Nichole
Abstract : This short essay represents an edited version of a larger work-in-progress article regarding the crucial role of storytelling, listening, and acknowledgment when working with survivors of trauma and abuse.